JOURNALISTS’ ETHICAL CODES IN SERBIA THROUGHOUT HISTORY - Cvejić, Bojan (Political Review, 2025)
Media in Serbia today massively violate ethical and professional standards prescribed by the Code of Journalists of Serbia, as evidenced by the annual monitoring conducted by the Press Council. Although it may not appear so at first glance, journalism in these regions has a long history of establishing ethical rules through written documents, i.e., journalists' codes, albeit with significant delays compared to developed countries. The first such code was adopted as early as 1965. However, it is not easy to find all the journalists' codes throughout history in professional, academic, or online literature, making it challenging to draw conclusions about which rules are deeply rooted in the journalistic community and which are more recent. It also complicates efforts to analyze media content throughout history in terms of ethics. The aim of this Paper was to identify and collect archival material in this field, systematize all the documents, and present the development of media ethics through the history of journalists' codes by analyzing their content in the subsequent text.
Keywords: ethics; media; code; journalists' code; history; journalism